Walking the "Course of Blessed Tears": Cassiodorus's Expositio Psalmorum and the Emergence of Penitential Psalm Devotion - Glowasky, Michael (Journal of medieval religious cultures, 2024)
While Cassiodorus's Exposition of the Psalms (ca. 538–570) is commonly cited as the first recorded instance we have of the seven Penitential Psalms being grouped together as a distinct set, it is typically believed that the origin of this set, and thus the devotional practices that grew out of it, can be traced to an earlier date. As a result, Cassiodorus's commentary on the Psalms has not received the attention it deserves. However, the author suggests in this article that it was Cassiodorus's unique rhetorical approach to the interpretation of these Psalms that established penitential psalm devotion and allowed it to flourish throughout the medieval period. This is because his interpretation of these psalms elevates them to a means by which the guilty sinner may receive pardon for their sins.